Alterações clínicas do periodonto durante a gestação - Serrano, Mírian Navarro [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study assessed the prevalence of major changes periodontal manifested during pregnancy. Data were obtained by analyzing the following variables, listed in the medical records of pregnant women attended at the Clinical Dental Care Program for Pregnant Woman, the Unesp / FOA: age, education, socio-economic oral change, gingival bleeding, use of fluoride, frequency of brushing, flossing and presence of plaque retentive factors. We also analyzed the following indicators: CPI, PIP and SOH-I. Of the 698 charts reviewed, 55.34% of the women had signs of periodontal disease, 7.6% with insertion loss larger than 4mm. The SOH-I in the 1st visit was good in 17.2%, 49.1% regular and 33.7% bad. After completion of treatment were obtained SOH-I 37.3% good, 44.4% regular and 18.3% bad. There was gingival bleeding by 65.1%, 14.2% had some type of change in the oral cavity, such as swollen gums and red. Regarding oral hygiene habits, 94.6% of patients reported brushing their teeth twice or more a day, but 60.2% responded to flossing infrequently. The presence of plaque retentive factors was observed in 52.2% of cases. It was concluded that gingivitis and gingival bleeding were the main clinical manifestations of the periodontium during pregnancy. Educational and preventive programs targeted to this group promote oral health during pregnancy and avoid the development of severe periodontal problems in the future

Objetivou-se verificar a prevalência das principais alterações periodontais manifestadas durante a gestação. Os dados foram obtidos por meio da análise das seguintes variáveis, constantes nas fichas clínicas das gestantes, atendidas na Clínica do Programa de Atenção Odontológica à Gestante, da Unesp/ FOA: idade, escolaridade, nível sócio-econômico, alteração bucal, sangramento gengival, uso de flúor, freqüência de escovação, uso de fio dental e presença de fatores retentivos de placa. Analisou-se também os seguintes indicadores: CPI, PIP e IHOS. Dos 698 prontuários analisados, 55,34% das gestantes apresentavam sinais da doença periodontal; 7,6% com perda de inserção maior que 4mm. O IHOS na 1ª consulta foi ótimo em 17,2 %, 49,1% regular e 33,7% ruim. Após término do tratamento, obteve-se IHOS 37,3% ótimo, 44,4% regular e 18,3% ruim. Verificou-se sangramento gengival em 65,1%, 14,2% algum tipo de alteração intrabucal, como gengiva edemaciada e avermelhada. Quanto aos hábitos de higiene bucal, 94,6% das pacientes relataram escovar os dentes duas vezes ou mais ao dia; porém, 60,2% responderam fazer uso do fio dental raramente. Conclui-se que a gengivite e o sangramento gengival foram as principais manifestações clínicas do periodonto durante a gestação e que Programas educativo-preventivos direcionados a este grupo promovem saúde bucal durante a gravidez e evitam o desenvolvimento de problemas bucais no futuro
Keywords: Higiene bucal; Periodontite; Gravidez; Oral hygiene